2008
DOI: 10.1182/blood-2007-10-116582
|View full text |Cite
|
Sign up to set email alerts
|

In adults with standard-risk acute lymphoblastic leukemia, the greatest benefit is achieved from a matched sibling allogeneic transplantation in first complete remission, and an autologous transplantation is less effective than conventional consolidation/maintenance chemotherapy in all patients: final results of the International ALL Trial (MRC UKALL XII/ECOG E2993)

Abstract: An international collaboration was set up to prospectively evaluate the role of allogeneic transplantation for adults with acute lymphoblastic leukemia (ALL) and compare autologous transplantation with standard chemotherapy. Patients received 2 phases of induction and, if in remission, were assigned to allogeneic transplantation if they had a compatible sibling donor. Other patients were randomized to chemotherapy for 2.5 years versus an autologous transplantation. A donor versus no-donor analysis showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
529
10
11

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 689 publications
(571 citation statements)
references
References 34 publications
21
529
10
11
Order By: Relevance
“…Because a high incidence of relapse is the main cause of treatment failure in adults with ALL, the use of allogeneic stem cell transplantation (SCT) as post-remission therapy has become a widely-accepted strategy. In the setting of myeloablative conditioning (MAC), the graft-versusleukemia (GVL) effect for adult ALL has been definitely confirmed from several "donor vs. no donor" comparisons [8][9][10]. However, nonrelapse mortality (NRM) may counterbalance that favorable overall outcome observed after MAC-SCT in patients with advanced age or comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Because a high incidence of relapse is the main cause of treatment failure in adults with ALL, the use of allogeneic stem cell transplantation (SCT) as post-remission therapy has become a widely-accepted strategy. In the setting of myeloablative conditioning (MAC), the graft-versusleukemia (GVL) effect for adult ALL has been definitely confirmed from several "donor vs. no donor" comparisons [8][9][10]. However, nonrelapse mortality (NRM) may counterbalance that favorable overall outcome observed after MAC-SCT in patients with advanced age or comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies addressed this question in the younger patient population using a 'genetic' assignment that allocated patients to HSCT in first remission based on donor availability. The largest of these studies, the MRC UKALL XII/ECOG2993, demonstrated an OS benefit for HSCT in first remission for the Ph-negative cohort but this OS advantage was lost for patients older than 35 years-old or those with elevated WBC counts at diagnosis, mainly due to an increase in NRM with HSCT that reached 36% at 2 years [9]. These findings were later confirmed in an individual-patient-data meta-analysis that pooled results from 13 studies [22].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports demonstrate that ALL patients with high risk features (generally defined as older age, high WBC at diagnosis or high risk cytogenetics) do not benefit from transplant as compared to patients without these features, due to a considerable NRM that offsets the lower relapse rate entailed with HSCT [9,22]. Accordingly we defined high-risk in this cohort as WBC count at diagnosis of 30 3 10 9 /L or 100 3 10 9 /L for Bor T-cell ALL, respectively or MLL rearranged leukemia [23].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations